Post-national Family/Post-familial Nation: Family, Small Town, and Nation Talk in Marcos and Brocka - Tolentino, Rolando B. (Archīum Ateneo, 2024)
Post-national Family/Post-familial Nation: Family, Small Town, and Nation Talk in Marcos and Brocka